A high-temperature, high-strength, self-lubricating composite material and preparation method thereof
By filling the MAX phase metal cermet components and metal components into the porous high-temperature alloy framework structure, a high-temperature alloy/MAX-based self-lubricating composite material is formed, which solves the problem of coordination and uniformity of mechanical and friction properties of existing materials under high temperature conditions, and achieves the balance of high-temperature self-lubricating and mechanical properties.
Patent Information
- Application Number
- CN202411162254.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-23
AI Technical Summary
It is difficult for existing high-temperature alloy-based solid self-lubricating materials to take into account both high-temperature mechanical properties and self-lubricating properties, especially in high-temperature corrosion environments, high-speed and heavy-load conditions.
The porous high-temperature alloy framework structure is combined with the self-lubricating material of the MAX phase cermet component and the metal component, and a dense high-temperature alloy/MAX-based self-lubricating composite material is formed by sintering.
It has achieved excellent self-lubricating and grinding performance under high temperature conditions, and has good high-temperature mechanical properties, and is suitable for high-temperature bearing components.
Smart Images

Figure CN119016730B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of self-lubricating materials, and in particular to a high-temperature and high-strength self-lubricating composite material and a preparation method thereof. Background Art
[0002] The rapid development of industrial technology has put forward more stringent working requirements for many mechanical equipment, such as high temperature and long life requirements. This poses a huge challenge to the core component materials that constitute the relevant friction system. Taking the various moving parts such as bearings, bushings, gears in the aerospace industry as an example, in order to play a sufficient wide temperature range support, stability and lubrication role, the relevant materials are required to have excellent mechanical properties and friction reduction and wear resistance under high temperature oil-free lubrication conditions. However, existing high-temperature solid lubricating materials often have insufficient mechanical properties and are very sensitive to the ambient atmosphere and ambient temperature. Under extremely harsh conditions, such as high temperature, high-temperature corrosion environment, high speed, and alternating atmosphere and vacuum under heavy load conditions, the failure of related materials will be aggravated. Therefore, the development of new high-temperature solid self-lubricating materials with good friction properties and superior mechanical properties has become the focus of related technical fields.
[0003] In order to meet the high-temperature mechanical properties and self-lubrication requirements of solid self-lubricating composite materials, alloys with stable structure, strong antioxidant ability and good mechanical properties are usually used as the matrix of the composite material, and soft metals, metal oxides, metal fluorides and layered structures are used as lubricants. For example, the document (Wear, 310, (2014) 1-11) reported a nickel-aluminum-based self-lubricating material, which showed good lubrication effect from room temperature to 800°C by adding Ti3SiC2 and MoS2 as lubricants; the patent document with publication number CN109706370A disclosed a preparation method of in-situ synthesized MAX phase reinforced nickel-based high-temperature lubricating composite material, which introduced Ti3AlC2 lubricating material into nickel-based high-temperature alloy by powder metallurgy to obtain a MAX phase three-dimensional layered ceramic reinforced nickel-based composite material with high-temperature lubricity; the patent document with publication number CN106086525A disclosed a low-friction nickel A high-temperature self-lubricating composite material and its preparation method, using Ag, WS2, and graphite as lubricants, the composite material has low friction and high wear resistance from room temperature to 500°C; the patent document with publication number CN106086526A discloses a nickel-based self-lubricating composite material, which improves its friction and wear performance by adding a eutectic of CaF2 and BaF2 as a high-temperature lubricant; the patent document with publication number CN101463452A discloses an iron-based alloy-based self-lubricating composite material, using MoS2 and WS2 as lubricants, the material has excellent wear resistance at 500°C to 700°C and can achieve self-lubrication, and is suitable for high-temperature equipment sliding parts. However, the above-mentioned composite materials are all composites of metal matrix and a large number of layered compounds or soft metals on a microscopic scale, and cannot have good high-temperature mechanical properties.
[0004] It can be seen from this that the currently reported high-temperature alloy-based solid self-lubricating materials are difficult to achieve the coordinated unification of high-temperature mechanical and tribological properties. It is urgent to develop a new type of high-strength metal-based self-lubricating composite material to adapt to the application of high-temperature load-bearing components. Summary of the invention
[0005] The purpose of the present invention is to provide a high-temperature, high-strength self-lubricating composite material and a preparation method thereof, wherein the material can take into account both the excellent mechanical properties of high-temperature alloys and the low friction coefficient and wear rate of self-lubricating materials.
[0006] In a first aspect, the present invention provides a self-lubricating composite material, the composite material comprising a high-temperature alloy material and a self-lubricating material, the high-temperature alloy material is formed into a porous main skeleton structure, and the self-lubricating material is filled and compounded in the porous main skeleton structure;
[0007] Wherein, the high temperature alloy material comprises at least one of Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high temperature alloy;
[0008] The self-lubricating material comprises a MAX phase cermet component and a metal component;
[0009] The molecular formula of the MAX phase metal ceramic component is M n+1 AX n , n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, and X is C and / or N;
[0010] The metal component includes at least one of metals Cu, Ag, Pb, Ti, Al or V.
[0011] Optionally, the self-lubricating material accounts for 10% to 70% of the total volume of the composite material.
[0012] Optionally, the self-lubricating material accounts for 20% to 40% of the total volume of the composite material.
[0013] Optionally, the mass ratio of the MAX phase metal ceramic component to the metal component in the self-lubricating material is 0.5:99.5 to 99.5:0.5.
[0014] Optionally, the high-temperature alloy material includes a Ni-based high-temperature alloy.
[0015] Optionally, the MAX phase metal ceramic component includes Ti3AlC2 and / or doped (Ti,M')3AlC2, wherein M' includes at least one of Cr, V, Zr or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti or Al.
[0016] Optionally, a transition layer is formed between the self-lubricating material and the porous main skeleton structure, and the average thickness of the transition layer is 3 to 30 μm.
[0017] Optionally, the phase structure of the transition layer includes a Cu / Ni phase and a Ni / Ni3Al phase.
[0018] In a second aspect, the present invention provides a method for preparing the aforementioned self-lubricating composite material, comprising the following steps:
[0019] S1. Providing a high-temperature alloy material and a self-lubricating material, wherein the high-temperature alloy material is formed into a porous main skeleton structure, and the self-lubricating material is filled in the porous main skeleton structure;
[0020] S2. Sintering to obtain the composite material.
[0021] Optionally, in step S2, the sintering pressure is 30-1000 MPa, the sintering temperature is 700-1300° C., and the holding time is 5-200 min.
[0022] Optionally, the sintering pressure is 30-100 MPa, the sintering temperature is 850-1000° C., and the holding time is 5-30 min.
[0023] In summary, the present invention has at least one of the following beneficial effects:
[0024] 1. The high-temperature and high-strength self-lubricating composite material provided by the present invention has good high-temperature mechanical properties; in addition, the self-lubricating composite material has stable structural performance, and exhibits excellent self-lubricating and anti-friction properties, especially at high temperatures.
[0025] 2. The present invention provides a method for preparing a high-temperature, high-strength, self-lubricating composite material, in which a metal skeleton with a multi-structured surface is made of a high-temperature alloy, and a self-lubricating powder mixed with MAX powder and metal powder is filled therein, which can be sintered to form a metallurgical interface bonding of an alloy / metal / layered metal ceramic structure with the high-temperature alloy to ensure the overall structural strength and stability of the composite material. By regulating the volume ratio and surface structure of the two materials, the mechanical properties and self-lubricating characteristics of the composite material can be regulated, so that it exhibits mechanical and friction properties suitable for the requirements over a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 Schematic diagram of the distribution of different high-temperature alloy skeletons and self-lubricating materials in an embodiment of the present invention;
[0028] Figure 2 This is a schematic diagram of the distribution of the high-temperature alloy skeleton and the self-lubricating material in Example 1;
[0029] Figure 3 is the XRD spectrum of the composite material sintered at 900° C. with a lubricating phase volume fraction of 30% in Example 1;
[0030] Figure 4 The interface structure of the composite material sintered at 900°C with a lubricating phase volume fraction of 30% in Example 1;
[0031] Figure 5is the friction coefficient curve of the composite material sintered at 900°C with a lubricating phase volume fraction of 30% and the high-temperature alloy of Example 1;
[0032] Figure 6 is the XRD spectrum of the composite material sintered at 1000° C. with a lubricating phase volume fraction of 30% in Example 2;
[0033] Figure 7 The interface structure of the composite material sintered at 1000°C with a lubricating phase volume fraction of 30% in Example 2;
[0034] Figure 8 is the friction coefficient curve of the composite material sintered at 1000°C with a lubricating phase volume fraction of 30% and the high-temperature alloy of Example 2;
[0035] Fig. 9 is the XRD spectrum of the composite material sintered at 900° C. with a lubricating phase volume fraction of 35% in Example 3;
[0036] Fig.10 The interface structure of the composite material sintered at 900°C with a lubricating phase volume fraction of 35% in Example 3;
[0037] Fig.11 is the friction coefficient curve of the composite material sintered at 900°C with a lubricating phase volume fraction of 35% and the high-temperature alloy of Example 3;
[0038] Fig.12 Schematic diagram of the high-temperature alloy skeleton of the 3D printed topological structure in Example 4. DETAILED DESCRIPTION
[0039] The present invention provides a high-temperature, high-strength, self-lubricating composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0040] High-temperature alloys refer to a type of metal material that can work for a long time at a high temperature of more than 600°C and under certain stress. Typical high-temperature alloys mainly include iron-based, nickel-based, cobalt-based, titanium-based, molybdenum-based, niobium-based or intermetallic compound-based high-temperature alloys. Among them, intermetallic compound-based high-temperature alloys refer to high-temperature alloy materials with compounds with specific crystal structures formed between two or more metals, such as Ni3Al-based, NiAl-based, Ti3Al-based, TiAl-based and Fe3Al-based. High-temperature alloys have excellent high-temperature strength, good oxidation resistance and thermal corrosion resistance, fatigue performance and fracture toughness and other comprehensive properties, and are mainly used in the aerospace and energy fields. Taking various moving parts such as bearings, sleeves, gears in the aerospace industry as an example, in order to play a sufficient wide temperature range support, stability and lubrication role, the relevant materials are required to have excellent mechanical properties and wear reduction and wear resistance under high-temperature oil-free lubrication conditions. However, existing high-temperature solid lubricating materials often have insufficient mechanical properties and are very sensitive to the ambient atmosphere and ambient temperature. Under extremely harsh conditions, such as high temperature, high-temperature corrosion environment, high speed, and alternating atmosphere and vacuum under heavy load conditions, the failure of related materials will be aggravated. Therefore, the development of new high-temperature solid self-lubricating materials with good friction properties and superior mechanical properties has become the focus of the relevant technical field. However, the solid self-lubricating composite materials reported in the prior art are usually a composite of a high-temperature alloy matrix and a large number of layered compounds or soft metal lubricating materials on a microscopic scale, which cannot have good high-temperature mechanical properties. After long-term research, the inventors have creatively proposed a high-temperature and high-strength self-lubricating composite material and a preparation method thereof. The composite material is composed of two materials including a high-temperature alloy material and a MAX-based self-lubricating material, wherein the high-temperature alloy material includes at least one of a Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high-temperature alloy, and the MAX-based self-lubricating material includes a MAX phase metal ceramic component and a metal component, and the metal component includes a metal single substance or alloy such as Cu, Ag, Pb, Ti, Al or V. Its preparation method includes, by 3D printing, powder metallurgy, casting or machining methods, a regular or irregular porous high-temperature alloy skeleton such as a honeycomb, a circle, a square, a diamond, etc. is obtained, and the holes can be connected or not connected, and can be uniform or uneven. Then the MAX-based self-lubricating material powder is filled and then subjected to powder metallurgy sintering to finally obtain a dense high-temperature alloy / MAX-based self-lubricating composite material.The high-temperature, high-strength self-lubricating composite material of the present invention has a porous skeleton structure formed by a high-temperature alloy matrix, and a MAX-based self-lubricating material is compounded in the porous skeleton structure, which has the advantages of both high-temperature alloys and MAX self-lubricating materials, and has good room temperature and high-temperature strength and self-lubricating wear resistance, especially at high temperatures. It shows good stability, mechanical properties and high-temperature self-lubricating wear resistance, and can achieve self-regulation of the performance of the composite material by regulating the proportion and distribution of the two types of materials. Such materials can be processed into key wear-resistant support components in high-temperature sliding mechanisms of various shapes such as planes, arc surfaces, and fan-shaped surfaces such as high-temperature bearings, sleeves, and fan plates, and are used in high-temperature friction conditions. The present invention is obtained on this basis.
[0041] In some embodiments of the present invention, a self-lubricating composite material is provided, the composite material comprising a high-temperature alloy material and a self-lubricating material, the high-temperature alloy material is formed into a porous main skeleton structure, and the self-lubricating material is filled and compounded in the porous main skeleton structure; please refer to Figure 1 , Figure 1 Different porous high-temperature alloy main skeleton structures and the distribution of self-lubricating materials are shown. The porous high-temperature alloy skeleton is a connected structure with different types of holes distributed. The holes can be regular or irregular shapes such as honeycomb, round, square, diamond, etc. The holes can be connected or not. The self-lubricating material described in the present invention is distributed in the holes.
[0042] Wherein, the high temperature alloy material comprises at least one of Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high temperature alloy;
[0043] The self-lubricating material comprises a MAX phase cermet component and a metal component;
[0044] The molecular formula of the MAX phase metal ceramic component is M n+1 AX n , n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, and X is C and / or N;
[0045] The metal component includes at least one of Cu, Ag, Pb, Ti, Al or V. The metal can be either a single metal or an alloy.
[0046] In some embodiments of the present invention, the intermetallic compound-based high-temperature alloy is preferably at least one of Ni3Al-based, NiAl-based, Ti3Al-based, TiAl-based or Fe3Al-based intermetallic compounds.
[0047] In some embodiments of the present invention, the high-temperature alloy material includes a Ni-based high-temperature alloy; preferably, the MAX phase metal ceramic component M includes at least one of Ti, V, Cr, Zr, and Nb; A includes at least one of Al, Si, P, S, Ga, or Pb; more preferably, the MAX phase metal ceramic component includes Ti3AlC2 and / or doped (Ti, M')3AlC2, wherein M' includes at least one of Cr, V, Zr, or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti, or Al; more preferably, the MAX phase metal ceramic component includes Ti3AlC2, and the metal component includes Cu.
[0048] In some embodiments of the present invention, the self-lubricating material accounts for 10 to 70% of the total volume of the composite material; preferably, the self-lubricating material accounts for 20 to 40% of the total volume of the composite material; more preferably, the self-lubricating material accounts for 25 to 40% of the total volume of the composite material; more preferably, the self-lubricating material accounts for 26 to 32% of the total volume of the composite material.
[0049] In some embodiments of the present invention, the mass ratio of the MAX phase metal ceramic component to the metal component is 0.5:99.5 to 99.5:0.5; preferably, the mass ratio of the MAX phase metal ceramic component to the metal component is 10:90 to 90:10; more preferably, the mass ratio of the MAX phase metal ceramic component to the metal component is 30:70 to 70:30.
[0050] In some embodiments of the present invention, a transition layer is formed between the self-lubricating material and the porous main skeleton structure, and the average thickness of the transition layer is 3 to 30 μm; preferably, the average thickness of the transition layer is 5 to 30 μm; more preferably, the average thickness of the transition layer is 8 to 25 μm; more preferably, the average thickness of the transition layer is 12 to 18 μm; more preferably, the average thickness of the transition layer is 14 to 16 μm.
[0051] In some embodiments of the present invention, the phase structure of the transition layer includes a Cu / Ni phase and a Ni / Ni3Al phase.
[0052] In some embodiments of the present invention, a method for preparing a self-lubricating composite material is provided, comprising the following steps:
[0053] S1. Providing a high-temperature alloy material and a self-lubricating material, wherein the high-temperature alloy material is formed into a porous main skeleton structure, and the self-lubricating material is filled in the porous main skeleton structure;
[0054] S2. Sintering to obtain the composite material.
[0055] In some embodiments of the present invention, in step S2, the sintering pressure is 30-1000 MPa, the sintering temperature is 700-1300°C, and the holding time is 5-200 min; preferably, the sintering pressure is 30-100 MPa; preferably, the sintering temperature is 700-1000°C, more preferably, the sintering temperature is 850-1000°C, more preferably, the sintering temperature is 850-950°C; preferably, the holding time is 5-100 min, more preferably, the holding time is 5-30 min.
[0056] In the present invention, the MAX phase metal ceramic component can be pure M n+1 AX metal ceramics can also be doped with a small amount of second-class compounds, which include nitrides (Si3N4, AlN, etc.), borides (TiB2, ZrB2, etc.), oxides (Al2O3, MoO3), sulfides (MoS2, WS2, etc.) or intermetallic compounds (Ti3Al, Ni3Al, etc.). Among them, the addition of hard second-class compounds with high melting point and high shear strength that are difficult to oxidize will play a role of dispersion strengthening, improving the strength of the material at high temperatures, but may be detached under the action of the grinding pair during the friction process to form abrasive particles, increasing the volume wear rate of the material; and the addition of low-melting-point oxides or the addition of second-class compounds that are oxidized to form low-melting-point oxides during the friction process will improve the self-lubricating properties of the material, such as TiB2 will form B3O2 during high-temperature friction, reducing the friction coefficient and volume wear rate. The doping amount of the second-class compound does not exceed 20wt%, preferably does not exceed 10wt%, and more preferably does not exceed 5wt%.
[0057] The present invention is further described below by means of specific examples. In the specific examples of the present invention, raw materials are commercially available unless otherwise specified, or are obtained by conventional preparation methods in the art.
[0058] Example 1
[0059] This embodiment provides a high-temperature, high-strength, self-lubricating composite material and a preparation method thereof, comprising the following steps:
[0060] S1. Provide high temperature alloy materials and self-lubricating materials. Specifically, the high temperature alloy material uses the nickel-based high temperature alloy model Incol738, please refer to Figure 2 In Example 1, a high-temperature alloy material is formed into a porous main skeleton structure by machining. The outer dimensions of the main skeleton structure are 20 mm*20 mm*20 mm, and the main skeleton structure includes a plurality of through holes evenly arranged axially parallel to the height direction of the main skeleton structure. The through holes are cylindrical with an inner diameter of 1 mm. The total volume of the plurality of through holes is 30 vol% of the total volume of the main skeleton structure.
[0061] The self-lubricating material is filled into the porous main skeleton structure so that the self-lubricating material accounts for 30 vol% of the total volume of the composite material. The self-lubricating material used in Example 1 includes a uniformly mixed Ti3AlC2 powder and Cu powder, wherein the mass ratio of Ti3AlC2 powder and Cu powder is 40:60, the particle sizes of Ti3AlC2 powder and Cu powder are 5um and 10um respectively, and the purity is above 99.9%. The specific filling steps include: using a graphite mold with an inner diameter of 30mm and a height of 100mm, inserting the mold lower pressure head, filling 10g of self-lubricating material powder, placing the porous main skeleton structure on the surface of the powder, and then filling 10g of self-lubricating material powder, followed by cold pre-pressing, and the strength of cold pre-pressing is 100MPa;
[0062] S2. Sintering: Place the pre-pressed mold into a spark plasma sintering furnace for vacuum sintering at a temperature of 900°C. Maintain vacuum in the furnace at a vacuum degree of 10 -3 Pa, the holding time is 10min, the sintering pressure is 50MPa, and the furnace is cooled to room temperature after holding. After demoulding, a high-temperature alloy-based self-lubricating composite material is obtained. The density of the sintered composite material is measured to be greater than 99%.
[0063] The X-ray diffractometer (XRD) was used to characterize the phase composition of the composite material. The XRD pattern of the composite material prepared in Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the phase structure of the composite material includes Cu / Ni phase, Cu phase, Ti3AlC2 phase and Ni / Ni3Al phase.
[0064] The microstructure of the composite material was characterized by scanning electron microscopy (SEM). Figure 4 As shown, from Figure 4 It can be seen that the composite material includes a black Ni-based high-temperature alloy, a gray-black transition layer, a gray-white metal Cu, and a layered Ti3AlC2 metal ceramic dispersed in the metal Cu. Figure 3 and Figure 4 It can be seen that after sintering, the Ni matrix phase in the main skeleton structure and the Cu phase and Ti3AlC2 phase of the self-lubricating material filled in the porous main skeleton structure are retained, and a diffusion reaction occurs between the self-lubricating material and the porous main skeleton structure to form a transition layer. The phase structure of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase, so that a close metallurgical bond is formed between the self-lubricating material and the main skeleton structure. The average thickness of the transition layer is 15μm.
[0065] The friction coefficient of the composite material obtained was tested in air at room temperature, 600°C and 800°C using an American Brooke friction tester. The friction pair was a high-temperature alloy GH4169 ball, the friction load was 10N, and the friction coefficient was Figure 5 The average friction coefficient of the composite material prepared in Example 1 at room temperature was measured to be 0.334, and the wear rate was 6.18×10 -5 mm 3 / (N·m); the average friction coefficient at 600℃ is 0.319, the average friction coefficient at 800℃ is 0.271, and the wear rate is 1.26×10 - 6 mm 3 / (N·m). The experimental results show that the nickel-based high-temperature alloy / Ti3AlC2+Cu self-lubricating composite material prepared in Example 1 has excellent self-lubricating performance during the friction process from room temperature to 800°C.
[0066] The high temperature compressive strength of the composite material was tested by a universal mechanical testing machine. The high temperature tensile strength of the composite material of Example 1 at 800° C. was measured to be 524 MPa, indicating that the composite material has excellent high temperature mechanical properties.
[0067] Example 2
[0068] The difference between Example 2 and Example 1 is that in step S2, the sintering temperature is 1000° C., and the remaining preparation steps are the same as those in Example 1. A high-temperature alloy-based self-lubricating composite material is prepared, and the density of the sintered composite material is measured to be greater than 99.5%.
[0069] The phase composition of the composite material of Example 2 was characterized by the same method as Example 1. The XRD pattern of the high-temperature alloy-based self-lubricating composite material prepared in Example 2 was measured as follows: Figure 6 As shown, from Figure 6 It can be seen that the phase structure of the high-temperature alloy-based self-lubricating composite material of Example 2 includes Cu / Ni phase, Cu phase, Ti3AlC2 phase and Ni / Ni3Al phase.
[0070] The microstructure of the composite material of Example 2 was characterized by the same method as Example 1. The microstructure of the composite material prepared in Example 2 was measured as follows: Figure 7 As shown, from Figure 7 It can be seen that the composite material includes a black Ni-based high-temperature alloy, a gray-black transition layer, a gray-white metal Cu, and a layered Ti3AlC2 metal ceramic dispersed in the metal Cu. Figure 6 and Figure 7It can be seen that after sintering, the Ni matrix phase in the main skeleton structure and the Cu phase and Ti3AlC2 phase of the self-lubricating material filled in the porous main skeleton structure are retained, and a diffusion reaction occurs between the self-lubricating material and the porous main skeleton structure to form a transition layer. The physical phase structure of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase, so that a close metallurgical bond is formed between the self-lubricating material and the main skeleton structure. The average thickness of the transition layer in Example 2 is 20μm.
[0071] The friction performance of the composite material of Example 2 was tested by the same method as Example 1. The friction coefficient of the composite material of Example 2 was as follows: Figure 8 As shown, the average friction coefficient of the composite material prepared in Example 2 at room temperature is 0.556, and the wear rate is 5.36×10 -4 mm 3 / (N·m); the average friction coefficient at high temperature of 800℃ is 0.488, and the wear rate is 6.3×10 - 6 mm 3 / (N·m)mm 3 / (N·m). The experimental results show that the nickel-based high-temperature alloy / Ti3AlC2+Cu self-lubricating composite material of Example 2 has good room temperature and high temperature self-lubricating properties, but the self-lubricating properties are significantly reduced compared with those of Example 1. The main reason is that the interface width of the transition layer of the composite material increases, and the amount of Ni3Al generated increases, and its lubricating properties are worse than Ti3AlC2, resulting in a significant weakening of the lubricating properties of the composite material.
[0072] The high temperature compressive strength of the composite material of Example 2 was tested in the same manner as in Example 1. The high temperature tensile strength of the composite material of Example 2 at 800°C was measured to be 611 MPa, indicating that the composite material has excellent high temperature mechanical properties, and the high temperature tensile strength of Example 2 is significantly better than that of Example 1. The main reason for this is that the interface width of the transition layer of the composite material is increased, and the combination of the self-lubricating phase and the high temperature alloy matrix is stronger.
[0073] Example 3
[0074] The difference between Example 3 and Example 1 is that the total volume of the multiple through holes of the high-temperature alloy material provided in step S1 of Example 3 is 35 vol% of the total volume of the main skeleton structure; after the self-lubricating material is filled, the self-lubricating material accounts for 35 vol% of the total volume of the composite material; the remaining preparation steps are the same as those in Example 1, and a high-temperature alloy-based self-lubricating composite material is prepared. The density of the sintered composite material is measured to be greater than 99%.
[0075] The phase composition of the composite material of Example 3 was characterized by the same method as Example 1. The XRD pattern of the high-temperature alloy-based self-lubricating composite material prepared in Example 3 is shown in FIG. Fig. 9 As shown, the phase structure of the high-temperature alloy-based self-lubricating composite material includes Cu / Ni phase, Cu phase, Ti3AlC2 phase and Ni / Ni3Al phase.
[0076] The microstructure of the composite material of Example 3 was characterized by the same method as Example 1. The microstructure of the composite material prepared in Example 3 is as follows: Fig.10 As shown, from Fig.10 It can be seen that the composite material includes a black Ni-based high-temperature alloy, a gray-black transition layer, a gray-white metal Cu, and a layered Ti3AlC2 metal ceramic dispersed in the metal Cu. Fig. 9 and Fig.10 It can be seen that after sintering, the Ni matrix phase in the main skeleton structure and the Cu phase and Ti3AlC2 phase of the self-lubricating material filled in the porous main skeleton structure are retained, and a diffusion reaction occurs between the self-lubricating material and the porous main skeleton structure to form a transition layer. The physical phase structure of the transition layer includes Cu / Ni phase and Ni / Ni3Al phase, so that a close metallurgical bond is formed between the self-lubricating material and the main skeleton structure. The average thickness of the transition layer in Example 3 is 20μm.
[0077] The friction performance of the composite material of Example 3 was tested by the same method as Example 1. The friction coefficient curve is as follows: Fig.11 The average friction coefficient of the composite material prepared in Example 3 was measured to be 0.48 at room temperature, and the wear rate was 5.41×10 -5 mm 3 / (N·m); the average friction coefficient at 600℃ is 0.305, the average friction coefficient at 800℃ is 0.28, and the wear rate is 4.46×10 -6 mm 3 / (N·m) and 2.7×10 -6 mm 3 / (N·m). The experimental results show that the nickel-based high-temperature alloy / Ti3AlC2+Cu self-lubricating composite material of Example 3 has good room temperature and high temperature self-lubricating properties, but its self-lubricating properties are worse than those of Example 1. The main reason is that the interface width of the transition layer of the composite material increases, and the amount of Ni3Al generated increases, and its lubricating properties are worse than Ti3AlC2, resulting in a significant weakening of the lubricating properties of the composite material.
[0078] The high temperature compressive strength of the composite material of Example 3 was tested in the same manner as in Example 1. The high temperature tensile strength of the composite material of Example 3 at 800°C was measured to be 421 MPa, indicating that the composite material has excellent high temperature mechanical properties, and the high temperature tensile strength of Example 3 is lower than that of Example 1, which is presumably mainly due to the reduction in the volume fraction of the high temperature alloy in the composite material of Example 3.
[0079] Example 4
[0080] The difference between Example 4 and Example 1 is that in step S1 of Example 4, the porous nickel-based high-temperature alloy topological structure prepared by 3D printing is used to replace the porous nickel-based high-temperature alloy formed by machining in Example 1. The structure of the high-temperature alloy used is as follows: Fig.12 shown.
[0081] Through the above preparation process, the embodiments of the present invention can prepare a high-temperature alloy-based self-lubricating composite material with high density, good mechanical properties, high temperature resistance, and good self-lubricating effect, among which the self-lubricating performance of embodiment 1 is better than that of embodiments 2 and 3.
[0082] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A self-lubricating composite material, characterized in that: The composite material comprises a high-temperature alloy material and a self-lubricating material, wherein the high-temperature alloy material is formed into a porous main skeleton structure, and the self-lubricating material is filled and composited in the porous main skeleton structure; wherein the high-temperature alloy material comprises at least one of a Ni-based, Co-based, Fe-based, Ti-based, Mo-based, Nb-based or intermetallic compound-based high-temperature alloy; the self-lubricating material comprises a MAX phase metal ceramic component and a metal component, wherein the mass ratio of the MAX phase metal ceramic component to the metal component is 30:70 to 70:30; the MAX phase metal ceramic component is M n+1 AX n Metal ceramics and doped second-class compounds, wherein n=1, 2 or 3, M includes at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Sc or Ta, A includes at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Tl or Pb, X is C and / or N, the second-class compounds include nitrides, borides, oxides, sulfides or intermetallic compounds, and the doping amount of the second-class compounds is greater than 0 and does not exceed 20wt%; the metal component includes at least one of metal Cu, Ag, Pb, Ti, Al or V; the preparation method of the self-lubricating composite material comprises the following steps: S1. providing a high-temperature alloy material and a self-lubricating material powder, the high-temperature alloy material is formed into a porous main skeleton structure, the self-lubricating material powder is pre-pressed and filled in the porous main skeleton structure, and the self-lubricating material powder accounts for 20% to 40% of the total volume of the composite material; S2. Sintering and molding, sintering the pre-pressed high-temperature alloy material and self-lubricating material powders, the sintering pressure is 50-100 MPa, to prepare the composite material, the density of the composite material is greater than 99%, a metallurgical interface bonding of an alloy / metal / layered metal ceramic structure is formed between the self-lubricating material and the high-temperature alloy material of the composite material, a transition layer is formed between the self-lubricating material and the porous main skeleton structure, and the average thickness of the transition layer is 3-30 μm.
2. The self-lubricating composite material according to claim 1, characterized in that: The high temperature alloy material includes a Ni-based high temperature alloy.
3. The self-lubricating composite material according to claim 1 or 2, characterized in that: The M n+1 AX n The metal ceramic includes Ti3AlC2 and / or doped (Ti,M')3AlC2, wherein M' includes at least one of Cr, V, Zr or Nb; the metal component includes Cu and / or Cu-M" alloy, wherein M" includes at least one of Ni, Sn, Cr, Nb, Ag, Pb, Ti or Al.
4. The self-lubricating composite material according to claim 1 or 2, characterized in that: In step S2, the sintering temperature is 700-1300°C, and the holding time is 5-200 minutes.
5. The self-lubricating composite material according to claim 1 or 2, characterized in that: In step S2, the sintering temperature is 850-1000°C, and the holding time is 5-30 minutes.
Citation Information
Patent Citations
Iron based high temperature self-lubricating composite material and its preparation
CN101463452A
Low-friction nickel base high-temperature self-lubricating composite material and preparation method thereof
CN106086525A
High-temperature-resistance wide-temperature-region self-lubricating composite material and preparation method thereof
CN106086526A
Preparation method for in-situ synthetic MAX phase reinforced nickel-based high-temperature lubricating composite material
CN109706370A
Ni-base alloy / ceramic composite material and preparing method thereof
CN105648276A